Application Research of Semi-coke Blending on a 600MW Anthracite "W" Flame Boiler - Guangwei CHEN; Jianping HUANG; Pengzhi XU (发电技术)
Through the coal quality analysis and comparison between semi-coke powder and design anthracite, the systematic analysis was taken to research the feasibility of semi-coke blending on a 600MW anthracite "W" flame boiler. The results show that it is technically feasible to blend semi-coke in this power plant. The limit of blending semi-coke is up to 3 coal mills controlled-by the load capacity. Considering the extremely strong abrasion characteristics of semi-coke, anti-wear reform is necessary to carry out on related equipment and components such as coal mills, pulverized coal separators, pulverized coal pipelines, burners and other equipment and components before blending, the perform subsequent operation and maintenance are very important either. The thermal efficiency of the boiler will not be reduced by blending of semi-coke, and due to the substantial reduction of the comprehensive dust content and sulfur content of the fuel, the blending will bring great environmental benefits and economic benefits. When the difference between semi-coke and coal is less than 220 yuan/ton, the blending semi-coke has profit, and the smaller the difference, the greater the profit.